2022
DOI: 10.3390/jpm12101545
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Processes during Recovery: Moving toward Personalized Spine Surgery Outcomes

Abstract: This paper focuses on a novel application of personalized medicine: the ways one thinks about health (i.e., appraisal processes) as relevant predictors of spine-surgery response. This prospective longitudinal cohort study (n = 235) investigated how appraisal processes relate to outcomes of spinal decompression and/or fusion surgery, from pre-surgery through one-year post-surgery. Patient-reported outcomes assessed spine-specific disability (Oswestry Disability Index (ODI)), mental health functioning (Rand-36 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…One notable factor of particular relevance to personalized medicine is cognitive-appraisal processes (i.e., how people recall past experiences and to whom they compare themselves) [ 10 ]. Past research has documented that appraisal processes are relevant to chronic pain [ 11 , 12 , 13 , 14 ] and spine-specific disability and mental-health functioning and suggested that such processes are modifiable targets of intervention [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…One notable factor of particular relevance to personalized medicine is cognitive-appraisal processes (i.e., how people recall past experiences and to whom they compare themselves) [ 10 ]. Past research has documented that appraisal processes are relevant to chronic pain [ 11 , 12 , 13 , 14 ] and spine-specific disability and mental-health functioning and suggested that such processes are modifiable targets of intervention [ 15 ].…”
Section: Introductionmentioning
confidence: 99%